Incidence estimates of hand and upper extremity injuries in Italy - Marco Giustini; Anna de Leo; Andrea Leti Acciaro; Giorgio Pajardi; Carlo Mamo; Fabio Voller; Francesco Fadda; Gianni Fondi; Alessio Pitidis (Istituto Superiore di Sanità, 2015)
OBJECTIVE: The purpose of this investigation is to estimate the incidence rates of upper extremity injuries and to give an overview of the most frequent diagnoses. MATERIALS AND METHODS: Two population databases were queried for all injuries in the upper extremities, the SINIACA-IDB (S-IDB: Emergency Department Injury Database in Italy) and the Hospital Discharge Register (HDR). The diagnoses codes of hand trauma were selected from both databases in order to estimate the national incidence rate. RESULTS: According to the S-IDB data of year 2011, total 1 479 510 ED attendances per year in Italy were estimated with an upper extremity injury (incidence rate: 2491 per 100 000 persons/year). About 880 816 Emergency Department (ED) attendances per year are due to hand injuries, while over 653 336 attendances per year concern arm injuries. The incidence rates are 1483 and 1100 per 100 000 person/year respectively. About 201 940 hospitalizations are observed in the HDR because of upper extremity injuries (incidence rate: 340 per 100 000 persons/year). Males have higher incidence rate (387 vs 280 per 100 000 persons per year). The trend in the incidence rates for the age group of inpatients shows two peaks: at age 12 (400 cases per 100 000 persons/year), and in the older age groups (700 cases per 100 000 persons/year).